ASCL1 regulates neurodevelopmental transcription factors and cell cycle genes in brain tumors of glioma mouse models. Issue 12 (23rd June 2020) - Vue, Tou Yia; Kollipara, Rahul K.; Borromeo, Mark D.; Smith, Tyler; Mashimo, Tomoyuki; Burns, Dennis K.; Bachoo, Robert M.; Johnson, Jane E.
Abstract: Glioblastomas (GBMs) are incurable brain tumors with a high degree of cellular heterogeneity and genetic mutations. Transcription factors that normally regulate neural progenitors and glial development are aberrantly coexpressed in GBM, conferring cancer stem‐like properties to drive tumor progression and therapeutic resistance. However, the functional role of individual transcription factors in GBMs in vivo remains elusive. Here, we demonstrate that the basic‐helix–loop–helix transcription factor ASCL1 regulates transcriptional targets that are central to GBM development, including neural stem cell and glial transcription factors, oncogenic signaling molecules, chromatin modifying genes, and cell cycle and mitotic genes. We also show that the loss of ASCL1 significantly reduces the proliferation of GBMs induced in the brain of a genetically relevant glioma mouse model, resulting in extended survival times. RNA‐seq analysis of mouse GBM tumors reveal that the loss of ASCL1 is associated with downregulation of cell cycle genes, illustrating an important role for ASCL1 in controlling the proliferation of GBM. Main Points: ASCL1 is coexpressed with neural stem cell/glial transcription factors in GBM. ASCL1 binds to genes that are important for cell proliferation and cancer in brain tumors. Loss of ASCL1 downregulates cell cycle genes and increase survival of glioma mouse model.